2017
DOI: 10.1038/cddiscovery.2017.71
|View full text |Cite
|
Sign up to set email alerts
|

Zinc-finger proteins in health and disease

Abstract: Zinc-finger proteins (ZNFs) are one of the most abundant groups of proteins and have a wide range of molecular functions. Given the wide variety of zinc-finger domains, ZNFs are able to interact with DNA, RNA, PAR (poly-ADP-ribose) and other proteins. Thus, ZNFs are involved in the regulation of several cellular processes. In fact, ZNFs are implicated in transcriptional regulation, ubiquitin-mediated protein degradation, signal transduction, actin targeting, DNA repair, cell migration, and numerous other proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
510
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 611 publications
(525 citation statements)
references
References 149 publications
(140 reference statements)
8
510
0
7
Order By: Relevance
“…We aligned LINC00115 sequence with other human RNAs and found that LINC00115 sequence from nucleotides 21-318 is almost identical to the 5 0 -UTR of zinc finger protein 596 (ZNF596) mRNA (99% identity) using BLAST (http:// blast.ncbi.nlm.nih.gov; Fig 5A and B). ZNF596 is a member of zinc finger protein family, which are functional diversity including transcriptional activation [33,34]. Moreover, LINC00115 knockdown inhibited ZNF596 mRNA ( Fig 5C) and protein ( Fig 5D) expression in 1123 and 528 GSCs.…”
Section: Znf596 Is Important For Linc00115-driven Gsc Tumorigenicitymentioning
confidence: 92%
“…We aligned LINC00115 sequence with other human RNAs and found that LINC00115 sequence from nucleotides 21-318 is almost identical to the 5 0 -UTR of zinc finger protein 596 (ZNF596) mRNA (99% identity) using BLAST (http:// blast.ncbi.nlm.nih.gov; Fig 5A and B). ZNF596 is a member of zinc finger protein family, which are functional diversity including transcriptional activation [33,34]. Moreover, LINC00115 knockdown inhibited ZNF596 mRNA ( Fig 5C) and protein ( Fig 5D) expression in 1123 and 528 GSCs.…”
Section: Znf596 Is Important For Linc00115-driven Gsc Tumorigenicitymentioning
confidence: 92%
“…Biological software has predicted that TGEV Nsp2, an 85-kDa protein encoded by the replicase gene, is composed of several functional domains, including a ZnF structure. ZnFs are independently folded domains containing approximately 30 amino acids, which are maintained by a zinc ion, and coordinated through cysteine and histidine residues in different combinations [38]. They are implicated in the regulation of several cellular processes, including replication, signal transduction, cell proliferation, and apoptosis [38,39].…”
Section: Pk-15 Cells [29] Andmentioning
confidence: 99%
“…ZnFs are independently folded domains containing approximately 30 amino acids, which are maintained by a zinc ion, and coordinated through cysteine and histidine residues in different combinations [38]. They are implicated in the regulation of several cellular processes, including replication, signal transduction, cell proliferation, and apoptosis [38,39]. Interestingly, the ZnF of TGEV Nsp14 is reported to potentially play a role in modulating the expression of IFN-β, TNF-α, and interferon-stimulated genes in ST cells [37].…”
Section: Pk-15 Cells [29] Andmentioning
confidence: 99%
“…Zinc can either participate, directly, in chemical catalysis or, indirectly, by maintaining protein structure or stability. For this reason, it has an important regulatory role in a wide variety of biological processes, acting as a catalyst for more than 300 enzymes and is contained within thousands of proteins, as a zinc finger domain . Zinc plays a key role in fundamental cellular processes such as DNA synthesis, RNA transcription, cell division, and activation, as well as in prevention of cell apoptosis .…”
Section: Introductionmentioning
confidence: 99%